Morphometric analysis of pituitary gland using magnetic resonance imaging in Indian subjects - Krishna GK; Harini Bopaiah; Anil Kumar Sakalecha; Lynn Joy (Asian Journal of Medical Sciences, 2024)
Background: Before the advent of magnetic resonance imaging (MRI), the radiological assessment of the hypothalamic-pituitary region relied on plain radiographs and computed tomography scans. However, contemporary medical practice now widely recognizes MRI as the preferred imaging modality for this purpose. The objective is to investigate variations in size and morphology of the pituitary gland associated with age and gender. Aims and Objectives: (a) The aims of this study were as follows: To establish normative measurements of pituitary gland in South Indian population. (b) To evaluate the relationship between gender, weight, height, and body mass index in different patients using conventional MRI sequences. Materials and Methods: This cross-sectional study, approved by the Institutional Review Board, included the enrolment of 140 normal individuals. The dimensions of the pituitary gland were assessed in 140 individuals exhibiting apparently normal pituitary gland function. The height and length of the pituitary gland were measured utilizing mid-sagittal T1-weighted images (T1-WI) obtained through MRI. The width of the pituitary gland was determined using coronal T1-WI, and the pituitary gland volume was subsequently calculated. Results: This study comprised 98 females and 102 males. The anteroposterior dimension, height, and volume of the pituitary gland showed statistically significant correlations with age (P<0.05), while the transverse dimension did not show a significant correlation with age (P>0.05). The shape of the pituitary gland was found to have statistically significant correlations with age and gender. Conversely, the transverse diameter, height, and volume of the pituitary gland showed no significant correlations. Conclusion: The findings underscore the importance of considering pituitary size, shape, and volume in the evaluation of neuroendocrine disorders.